Concentrations of toxic heavy metals and trace elements in raw milk of Simmental and Holstein-Friesian cows from organic farm - Pilarczyk, Renata (Springer Netherlands, 2013)
Concentrations of toxic heavy metals (cadmium (Cd), lead (Pb)) and major nutritional and trace elements (Ca, Mg, P, Cu, Fe, Mn, Se, Zn) were analyzed in the milk of Simmental (n = 20) and Holstein-Friesian (n = 20) cows from an organic farm. Elements were determined using inductively coupled plasma emission atomic spectrometry. The conducted research showed that the milk of Simmental cows was characterized by the more advantageous mineral composition and lower concentration of noxious heavy metals compared to the milk of Holstein-Friesian cows. In the milk of Simmental cows, significantly lower concentrations of Pb and Cd (P < 0.001) and Cu (P < 0.05) and significantly higher concentrations of Fe and Mg (P < 0.05) as well as nonsignificantly higher concentrations of Ca, Mn, and Se were found. In the milk of both breeds, very low Cu concentrations were recorded. The higher-than-recommended concentration of Pb in milk was also found. In the milk of both breeds, the significant positive correlations between concentrations of the following elements were observed: Pb–Cd, Pb–Se, Cd–Se, Cd–Mn, Zn–Cu, Zn–P, Ca–P, Ca–Mg, and Mg–P. The correlations between other elements within each of the analyzed breeds separately were also found.